Maritime Tourism Supports Improved Welfare of Coastal Communities in South Sulawesi (Torani Journal of Fisheries and Marine Science, 2021)
Indonesia has the potential for the beauty of its islands and coasts which are well known to foreign countries. Not only beautiful beaches, also stretches of coral reefs with hundreds of marine species, mangrove forests with their ecosystems are a panorama that can be found from Sabang to Maraoke. It is estimated that more than 21 marine tourism sites have been developed and become destinations for world and local tourists, in addition to locations that are still managed by the community. Foreign exchange contributions from the tourism sector continued to increase in 2018, the tourism sector's foreign exchange reached IDR 229.5 trillion, an increase of 15.4 percent on an annual basis. This study aims to describe the condition of marine tourism potential in South Sulawesi and its impact on local communities living around tourist sites and the development needed to improve the welfare of local communities. The research locations were on Lemo Beach, East Luwu Regency, Bira Bulukumba Beach and Makassar Lantebong Mangrove Tourism, taking 100 respondents. The research method is qualitative and analyzed descriptively by correlation and using Likers to assess its impact on people's welfare. The results of the study illustrate that in general, the role of the government, both local and provincial, is still needed, especially in environmental hygiene facilities, order for traders. The social impact on people's behavior shows that there is a change in the ability to communicate and interact more openly with a value of 1634. The economic impact shows a very large regional value due to the opening of new job opportunities which are a source of income for the local community with a value of 2250.